Improving Indigenous Food Sovereignty through sustainable food production: a narrative review - Rowe, Sarah; Brady, Catherine; Sarang, Rhea; Wiipongwii, Troy; Leu, Matthias; Jennings, Lydia; Peterson, Tomalita; Boston, Juan; Roach, Beth; Phillips, Jessica; Conrad, Zach (Frontiers in Sustainable Food Systems, 2024)
Indigenous communities in the United States (US) face substantial challenges including health disparities, food insecurity, and cultural disconnection. The Indigenous Food Sovereignty (IFS) movement seeks to address these hurdles through the restoration of traditional foodways in balance with the natural environment. Initiatives aimed at enhancing IFS have proliferated across the US in recent years and are receiving increasing attention from the federal government. While increasing community food production is an important component of IFS, initiatives centered around this goal have received relatively little attention in the literature. A better understanding of current efforts will elucidate the factors underlying their successes and challenges, supporting the development of effective future initiatives. This review characterizes IFS food production initiatives in the US and identifies topics for further research.